Phenotype overlap in glial cell populations: astroglia, oligodendroglia and NG-2(+) cells - Alghamdi, Badrah; Fern, Robert (Frontiers in Neuroanatomy, 2015)
The extent to which NG-2(+) cells form a distinct population separate from astrocytes is central to understanding whether this important cell class is wholly an oligodendrocyte precursor cell (OPC) or has additional functions akin to those classically ascribed to astrocytes. Early immuno-staining studies indicate that NG-2(+) cells do not express the astrocyte marker GFAP, but orthogonal reconstructions of double-labelled confocal image stacks here reveal a significant degree of co-expression in individual cells within post-natal day 10 (P10) rat optic nerve (RON) and rat cortex. Extensive scanning of various antibody/fixation/embedding approaches identified a protocol for selective post-embedded immuno-gold labelling. This first ultrastructural characterization of identified NG-2(+) cells revealed populations of both OPCs and astrocytes in P10 RON. NG-2(+) astrocytes had classic features including the presence of glial filaments but low levels of glial filament expression were also found in OPCs and myelinating oligodendrocytes. P0 RONs contained few OPCs but positively identified astrocytes were observed to ensheath pre-myelinated axons in a fashion previously described as a definitive marker of the oligodendrocyte lineage. Astrocyte ensheathment was also apparent in P10 RONs, was absent from developing nodes of Ranvier and was never associated with compact myelin. Astrocyte processes were also shown to encapsulate some oligodendrocyte somata. The data indicate that common criteria for delineating astrocytes and oligodendroglia are insufficiently robust and that astrocyte features ascribed to OPCs are likely to arise from misidentification.